Eksistensi Lembaga Keuangan Mikro Dalam Pembangunan Ekonomi Pedesaan - Thobby Wakarmamu (Jurnal Kajian Ekonomi dan Studi Pembangunan, 2014)
The empirical study of Micro Finance Institution (MFI) to investigate MFI performance in rural economics development perspective have been conducted in Java and off Java, in the early 2007 through PRA approach with group interview and individual in depth interview, involve the MFI board and customer. By using qualitative descriptive analysis approach of purposive chosen MFI, the result study obtained a following picture: (a) the existence of MFI is strategic role as intermediation of economics activities for the people who didn’t reach of conventional bank services; (b) in fact MFI services have been successful, but it was still bias of non agricultural business activities. The scheme of agricultural loan did not priorities, the budget of farming system support relatively small. That is not more then 10 % from total of MFI budget; (c) Critical success factors of agricultural MFI development are: legality of MFI institute, management capability, seed capital support, reasonable farming system, characteristic of farming system, training of MFI management and technical guidance of customer MFI; (d) Human resource evelopment, seed capital support and technical guidance of MFI customer are needed of the initiation and development of agricultural MFI. Key Words: Micro Finance Institution, Rural Economics Development